THE “GULAYAN SA PAARALAN” (SCHOOL VEGETABLE GARDEN) IN RESPONSE TO SUSTAINABLE DEVELOPMENT - Reynaldo B. Inocian; Lory M. Nuneza (European Scientific Journal, ESJ, 2015)
The demands of our growing population have done much damage to the environment in our quest for food; volumes of waste contribute to environmental risk (Akaateba & Yakubu, 2013). This study aimed to document the best practices of Talamban Elementary School’s “Gulayan sa Paaralan” in response to sustainable development. The following objectives were raised in order to answer the main problem: (1) determine the TESGP’s challenges and success stories; (2) assess the physical feature of the TES-GP; (3) identify the type of vegetables planted; (4) describe the gardening model used in the TES-GP, and (5) perceive the guidelines for its successful monitoring. The study employed a qualitative approach using phenomenology of Zahavi’s pre-reflective self-awareness of experience through interviews of a specific human subject named “Madam Green”. Personal experiences were categorized into retention, primal impression, and protention, which served as a self-manifestation of her stretched consciousness. An ocular observation of the garden was conducted to validate the interviews made. Data gathered were supplemented with periodic reports and other related studies. The “Gulayan sa Paaralan” (GP) was a modest replication of the “Gulayan ng Masa” (GM) served as one of the best practices of TES – created a vital contribution for its feeding program. Exasperations to the inimical attitude shown among the TES-GP’s stakeholders, resulted in the garden’s minimum involvement, insufficient landscaping and garden fixtures, no proper arrangement and classification of vegetables according to the specified garden models indicated no discouragement. Stretched consciousness of these realities, catapulted a vision to innovate organic fertilizers and pesticides in the enhancement of garden yields. Experiences swirled to a retention that mattered, a passion for environment, a coordination of the non-government organization was forged and protention for successful maintenance of the garden was regarded an anticipated proposal for action